Factors Affecting Customers’ Loyalty of Government Savings Bank, Buriram Branch, Buriram Province: Factors Affecting Customers’ Loyalty of Government Savings Bank, Buriram Branch, Buriram Province - Krasinram, Jaruwan; Panoram, Preecha; Srisuk, Kulkanya (RATANABUTH JOURNAL, 2025)
This research aimed to 1) investigate the factors affecting the customers’ loyalty of Government Savings Bank, Buriram Branch, Buriram Province, and 2) compare the factors affecting the customers’ loyalty of Government Savings Bank, Buriram Branch, Buriram Province, categorized by gender, age, marital status, education level, occupation, and monthly income. This study included a total of 40,694 participants. The sample comprised 396 people, determined using Taro Yamane's formula, with an error of 0.05. Data were collected using an accidental sampling. The tool used to collect the data was a questionnaire comprising three parts: a checklist, 5-point Likert scale, and open-ended questions. The discrimination ranged between 2.09 and 13.73, with a reliability of 0.95. The statistics used in the data analysis were frequency, percentage, mean, standard deviation, t-test, one-way analysis of variance (ANOVA), and post-hoc pairwise comparison test, according to Scheffe’s test. The findings revealed that: 1. The sample’s opinions on the factors affecting the customers’ loyalty of Government Savings Bank, Buriram Branch, Buriram Province, were overall at a high level. 2. The study comparing respondents' opinions on factors influencing customer loyalty toward the Government Savings Bank, Buriram Branch, found statistically significant differences at the .05 level based on gender, age, marital status, education level, occupation, and monthly income. Significant differences were particularly found in areas such as price sensitivity, reliability, responsiveness, assurance, empathy, word-of-mouth behavior, and purchase intention, while other factors showed no significant differences.